S78 Biologic therapy practices in severe asthma; outcomes from the UK severe asthma registry and survey of specialist opinion. (11th November 2022) - Mansur, AH; Gonem, S; Brown, T; Burhan, H; Chaudhuri, R; Dodd, JW; Pantin, T; Gore, R; Jackson, D; Menzies-Gow, A; Patel, M; Pavord, I; et al.
Abstract : Introduction and Objectives several biological treatments have become available for management of severe asthma. There is a significant overlap in the indication of these treatments with lack of consensus on the first-line biologic choice and switching practice in event of treatment failure. Herein we evaluate outcomes of biologic treatments through analysis of the UK Severe Asthma Registry (UKSAR), and survey of the UK severe asthma specialists' opinion. Methods records of patients registered in the UKSAR database and treated with biologics for severe asthma from January 2014 to August 2021 were analysed to explore biologic treatments practice. This was complemented by survey of opinion of severe asthma specialists. Results: a total of 2, 490 patients from 10 severe asthma centres were included in the study (mean age 51.3 years, 61.1% female, mean BMI 30.9kg/m 2 ). Biologics use included mepolizumab 1, 115 (44.8%), benralizumab 925 (37.1%), omalizumab 432 (17.3%), dupilumab 13 (0.5%), and reslizumab 5 (0.2%). The majority of patients (77.6%) achieved good clinical response and continued beyond the first year of treatment. Those on benralizumab were more likely to continue treatment longterm (93.9%) than those on mepolizumab (80%) or omalizumab (69.6%). Patients on omalizumab were younger and had earlier age of onset asthma than those prescribed mepolizumab or benralizumab. Patients prescribed mepolizumab and benralizumab had similar clinical characteristics. The first choice biologic differed between centres and changed over the study time period (figure). Experts' opinion also diverged in terms of biologic initiation choice and switching practice. Conclusion: We observed overall good clinical responses to biologics in severe asthma but with the caveat of significant variation in the prescribing choices amongst centres and experts necessitating further research and practice standardisation.